Role of Uroflowmetry in Patients of Benign Prostatic Hyperplasia Presenting with Lower Urinary Tract Symptoms: Uroflowmetry in Benign Prostatic Hyperplasia - Memon, Aijaz Hussain; Chandio, Mumtaz Ali; Bhellar, Zahoor Hussain; Rehman, Hameed Ur; Akhtar, Suhail; Bhurt, Asadullah (Pakistan Journal of Health Sciences, 2024)
Benign Prostatic Hyperplasia (BPH) is prevalent among aging men, causing Lower Urinary Tract Symptoms (LUTS) that can impact quality of life. Objective: To assess the role of uroflowmetry in determining Lower Urinary Tract Symptom (LUTS) severity in Benign Prostatic Hyperplasia (BPH) patients by examining correlations between symptom scores and uroflowmetric parameters (Qmax, Qavg, PVR, and voiding time). Methods: This cross-sectional study was conducted on sixty BPH male patients presenting with a spectrum of symptom scores based on IPSS. With a standard uroflowmeter, uroflowmetric parameters were determined and correlation coefficients and t-tests between parameters about most severe complaints yielded statistical analyses. Results: Uroflowmetric parameters were significantly different among severity groups of symptoms. Mean Qmax values decreased successively from 12.5 mL/s in mild to severe symptoms of 6.5 mL/s (p < 0.001). The same results were evident for average flow rates, as mean flows at mild were 8.0 mL/s vs severe of 4.0 mL/s (p < 0.001) Residual urine increased from 25 mL to 110 mL (p <0.001 and voiding times from 15 seconds up to 40 seconds (p <0.001). Correlation analysis revealed moderate positive and negative correlations between residual urine and IPSS (r = 0.60), Qmax (r = -0.54), and Qavg (r = -0.50) with IPSS scores (p < 0.001). Conclusion: The importance of uroflowmetry in clinical assessments and management methods was shown by the substantial correlation found between uroflowmetric parameters and the severity of BPH symptoms.